Human sentiment analysis using natural language processing - Shamya, Md. Shamiul Haque Khan; Fahim, Md. Shariar Hossain; Khan, Niaz Makhdum; Monir, K.M Mahfuzul; Hussain, Mubasshir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.